Marketing Mix Factors that Affect the Decision to Purchase Durian of Consumers in Lang Suan District, Chumphon Province - ศิวิลัย ศศิธร; เมืองแก่น เสาวภา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to: (1) study the level of marketing mix factors influencing durian consumers in Lang Suan District, Chumphon Province; (2) examine the level of consumer decision - making in purchasing durian in Lang Suan District, Chumphon Province; and (3) investigate the marketing mix factors affecting consumers’ decisions to purchase durian in Lang Suan District, Chumphon Province. The sample group consisted of 385 consumers who purchased durian directly from orchards and resided in Lang Suan District, Chumphon Province. Convenience sampling was employed to select the participants. The research instrument was a questionnaire, which demonstrated a reliability coefficient of 0.953 The data were analyzed using frequency, percentage, mean, standard deviation, and multiple regression analysis. The results revealed that: (1) among the marketing mix factors, price had the highest overall average score; (2) regarding purchasing decision-making, the highest mean score was found in the area of problem recognition; and (3) product, price, place (distribution channels), and promotion significantly influenced consumers’ durian purchasing decisions at the 0.05 level of statistical significance.